2014
DOI: 10.1117/1.jmi.1.1.015502
|View full text |Cite
|
Sign up to set email alerts
|

Detection of the spatial accuracy of a magnetic resonance and surgical computed tomography scanner in the region of surgical interest

Abstract: Abstract. In image-guided surgeries (IGSs) and radiology, images are the main source of information. As image data provide the differentiation between normal and abnormal tissues in the human, the images need to be reliable and they need to provide accurate spatial representation of the patient. This research concentrates on the accuracy assessment of IGS devices in general and then specifically on the spatial accuracy of a common magnetic resonance (MR) imager and a mobile three-dimensional surgical computed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…Computed tomography (CT) scans allow the same basic methodology without needing to digitise points manually. Compared to MRI, CT images give clearer three-dimensional images of the bony landmarks, and are more spatially accurate [15]. The main drawback is that CT scans are performed in the supine position rather than upright.…”
Section: Discussionmentioning
confidence: 99%
“…Computed tomography (CT) scans allow the same basic methodology without needing to digitise points manually. Compared to MRI, CT images give clearer three-dimensional images of the bony landmarks, and are more spatially accurate [15]. The main drawback is that CT scans are performed in the supine position rather than upright.…”
Section: Discussionmentioning
confidence: 99%
“…This significant difference between the tracking methods means that the EMTS instrument tip is tracked closer to the sensitive anatomical structures. Also, the OTS requires stable positioning and immobilization of the patient (Koivukangas 2012). Since the EMTS patient trackers are light and may be attached to the patient without for example skull clamps, rigid immobilization of the patient during procedures is not as critical.…”
Section: Discussionmentioning
confidence: 99%
“…This study used a specially designed accuracy assessment phantom (Koivukangas 2012) to assess the accuracy of a commercial surgical navigator, the StealthStation S7 (Medtronic Inc., Louisville, CO, USA). The navigator enabled the interchangeable use of both OTS and EMTS.…”
Section: Research Equipment and Methodsmentioning
confidence: 99%
“…However, the observed range of differences may warrant a larger safety factor and special circumstances may warrant additional consideration when planning the bony cut. The spatial accuracy of MRI in general has been described [4,19] and a small number of computer-navigated limbsparing resections utilizing fused CT and MRI models supplemented with intraoperative cutting templates have been studied [3,11,17,28]. In one study that quantitatively assessed margin status, it is important to consider that only nine of 26 cut planes of the pelvis were included in the margin analysis [28].…”
Section: Discussionmentioning
confidence: 99%
“…An updated assessment of the ability of MRI to accurately identify the osseous extent of tumor may allow the surgeon to better plan and consistently achieve margin-negative resections while potentially avoiding unnecessary morbidity from an overly extensive resection. Prior studies of MRI utilizing synthetic models have determined a high degree of spatial accuracy [19], and studies in mice have demonstrated that MRIs of tumor postresection were as accurate as the histopathologic assessment of the margin status in controlled study conditions [4]. However, the only known published data in humans, Sundaram et al [25] reported only qualitative evidence that MRI was the most accurate imaging modality for predicting the intramedullary extent of tumor.…”
Section: Introductionmentioning
confidence: 99%